Reactivity of eumelanin building blocks: A DFT study of monomers and dimers - Alves, Gabriel G.B. [UNESP]; Lavarda, Francisco C. [UNESP]; Graeff, Carlos F.O. [UNESP]; Batagin-Neto, Augusto [UNESP] (Elsevier, 2020)
Melanins are natural pigments with important biological properties and have been considered promising materials for several bio-electronic applications. In spite of it, until now there is no satisfactory understanding of the macromolecular structure of these compounds. In this work, we have employed electronic structure calculations to evaluate the local reactivity on monomeric building blocks of eumelanin and on a varied combination of these units (dimers). The reactivity studies were accomplished by Condensed-to-Atoms Fukui Indexes in a DFT approach. The results have evidenced a dominance order in the reactivity of the building units that guides the polymerization process of melanin. In addition, from the differences of the local reactivities it was possible to better understand the reactions that can take place during eumelanin synthesis and estimate how they could be influenced by experimental conditions.
Keywords: Electronic structure calculation; Fukui indexes; Melanin; Reactivity